2022
DOI: 10.1155/2022/7140024
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Polymorphisms and Risk of Kidney Posttransplant Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Objectives. The purpose of this study was to clarify the role of genetic factors on posttransplant diabetes mellitus (PTDM) risk. Methods. Relevant publications were systematically retrieved from PubMed, EMBASE, and the Cochrane Library up to December 2020. Data from eligible case-control and cohort studies were extracted for qualitative and quantitative analyses. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to estimate the association between gene polymorphisms and PTDM in the quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…PTDM occurs frequently after kidney transplantation and may be associated with graft loss, so factors that may increase the risk of this complication are being sought. Previous studies have shown that the pathophysiological changes leading to the development of PTDM are similar to those in type 2 diabetes mellitus [ 7 , 8 , 22 , 23 ]. It is believed that the risk factors leading to the occurrence of PTDM include factors associated with the development of type 2 diabetes mellitus, such as obesity, metabolic syndrome and a family history of type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTDM occurs frequently after kidney transplantation and may be associated with graft loss, so factors that may increase the risk of this complication are being sought. Previous studies have shown that the pathophysiological changes leading to the development of PTDM are similar to those in type 2 diabetes mellitus [ 7 , 8 , 22 , 23 ]. It is believed that the risk factors leading to the occurrence of PTDM include factors associated with the development of type 2 diabetes mellitus, such as obesity, metabolic syndrome and a family history of type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying this complication are factors affecting carbohydrate metabolism and pancreatic function, including genetic conditions. To date, many studies have considered the role of genetic polymorphisms as risk factors for the development of PTDM [ 8 ]. In particular, polymorphisms that have been confirmed to be associated with type 2 diabetes have been taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence of a genetic predisposition to PTDM, including established associations with the alleles HLA A28, A30, B27, and Bw42. Furthermore, a report has emphasized the association of TCF7L2 rs7903146 and SLC30A8 rs13266634 polymorphisms with a higher risk of PTDM [42][43][44][45]. Another study investigated the association of genetics with PTDM in a white UK renal transplant population; 26 SNPs were associated with PTDM, such as ATP5F1P6 rs1048482, DNAJC16 rs7533125, and CELA2B rs2861484 [46].…”
Section: Transplant Genetics Epigenetics and Their Association With Ptdmmentioning
confidence: 99%